4u-36=6(u-5)

Simple and best practice solution for 4u-36=6(u-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4u-36=6(u-5) equation:



4u-36=6(u-5)
We move all terms to the left:
4u-36-(6(u-5))=0
We calculate terms in parentheses: -(6(u-5)), so:
6(u-5)
We multiply parentheses
6u-30
Back to the equation:
-(6u-30)
We get rid of parentheses
4u-6u+30-36=0
We add all the numbers together, and all the variables
-2u-6=0
We move all terms containing u to the left, all other terms to the right
-2u=6
u=6/-2
u=-3

You can always share this solution

See similar equations:

| d?698=-271 | | -216=-6(1-5r) | | x-4-15=10 | | -7y+2(y-2)=31 | | 7(n=4)21 | | 3(-4-6b)=114 | | 181=84-w | | -140=5(4a-4) | | k-875=-750 | | y=4×5+12 | | k?875=-750 | | -8q=-88 | | -m+8(5-8m)=300 | | -3t=-78 | | 6x-4(3-2x)=4(x-4)-36 | | 41=6g+5 | | -8=w/8 | | 180=(3x+8)+(2x+24) | | -7-4n=21 | | 2h?-2h?3=13 | | n?14=49 | | 6x=15+5(x) | | 5u=-90 | | 3(15–2x)=7x+12–2x | | 9w=-90 | | 1.5h=5=2 | | q+-11=-63 | | 13x-118=6x-13 | | X+2÷3=x+34÷10 | | n=8=-4 | | x/24=30/15 | | -7+w=3 |

Equations solver categories